Contribution to EVA from Debt and Equity - Nelson Iván Araya-Canelo; Fernando Crespo Romero (Journal of Management and Business Studies, 2024)
Attempts to measure the economic value contributed to the company by the capital structure present various methodologies that bring together large working teams, whose proposals focus their analysis from the characteristics of the manager to models adjusted to their life cycle. This research addresses this problem by measuring the contribution to economic value through the capital structure, using the Economic Value Added (EVA) method as a basis, and then modifying its analysis variables to quantify the economic value added from debt and equity, which in this work is called Modified Added Economic Value (MEVA). A methodology is proposed to estimate the incremental economic value per monetary unit of financial debt acquired. The main results show that MEVA captures the disaggregated performance of debt and equity management. Moreover, to the extent that profit tax increases, debt is more desirable than equity issuance.